Old Things, Used Things. - LONG, PRISCILLA (Antioch Review)
The article focuses on the significance of old things. It explores the argument that old technology is not past technology, how people gave up on the common everyday skill of playing musical instruments upon the invention of the phonograph and the importance of handwriting to writing and reading before the invention of the keyboard and the screen.